Perforated Cystic Duplication in Cecum: A Rare Case - Kazez, Ahmet; Özel, Şeyhmus Kerem; Kocakoç, Ercan; Özercan, İbrahim Hanifi; Saraç, Mehmet (Fırat University, 2005)
Duplications are rare congenital anomalies which can be found in the gastrointestinal system from mouth to anus. Bleeding, intussusception, intestinal obstruction, volvulus and malignancy can complicate cystic duplications. A perforated cecal duplication cyst was detected in a 7-year-old boy operated with the findings of acute abdomen. The cyst was totally excised and the case is presented as a rare cause of acute abdomen.. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Duplikasyonlar gastrointestinal sistemde ağızdan anüse kadar herhangi bir yerde görülebilen nadir konjenital anomalilerdir. Kistik duplikasyonların kanama, invajinasyon, barsak obstrüksiyonu, volvulus, malignite gibi komplikasyonları görülebilir. Akut batın bulguları ile ameliyat edilen yedi yaşındaki erkek olguda, çekumda yerleşmiş ve perfore olmuş duplikasyon kisti tespit edildi. Total kist eksizyonu uygulanan olgu nadir bir akut batın nedeni olduğu için sunuldu.©2005, Fırat Üniversitesi, Tıp Fakültesi
Çekumda Duplikasyon Kisti Perforasyonu: Nadir Bir Olgu